Analysis of Business Development Strategies in Coffee Shop Business With QSPM Method Warkop Bekape Case Study - Alfariansyah, Septian; Tiara, Vonny (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
Warkop Bekape is a coffee shop located in Kemiling district Bandar Lampung, whose sales have experienced ups and downs due to the existence of similar businesses, has resulted in a decrease in incoming customers. The aim of this research is to determine the characteristics of business actors and the business profile of Warkop Bekape; to find out the business development strategy that will be used in the Warkop Bekape business. This research is a qualitative descriptive study with a sample of 10 people using interview techniques. Based on the research results, there are 12 internal and external factors with an IFE calculation of 3.552 and an EFE of 3.658. Based on the SWOT Matrix, the alternative strategy S – O 1 is to increase promotion through social media by creating appropriate content so that it attracts consumers, the alternative strategy S – O 2 is to collaborate with influencers, the alternative strategy W – O 1 is to add product variety steps, strategy alternative W – O 2 holds events to introduce products to consumers, alternative strategy S – T 1 develops new products and improves product quality, alternative strategy S – T 2 adds payment options, and alternative strategy W – T 1 expands the place, alternative strategy W – T 2 implements a pricing strategy, alternative strategy W – T 3 adds a new menu. Alternative strategies based on the QSPM ranking are adding new menus, holding events to introduce consumers to products, implementing pricing strategies, increasing promotions via social media by creating appropriate content to attract consumers, developing new products and improving product quality.